2019
DOI: 10.1080/09593985.2019.1641869
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being is associated with injury risk in adolescent elite athletes

Abstract: Objective: The purpose of this study was to explore the association of subjective well-being with injury and injury severity in adolescent elite athletes. Design: Prospective cohort study. Participants: Three hundred eighty-six adolescent elite athletes (age range 15-19), participating in seven different sports, were monitored repeatedly over 52 weeks using a valid questionnaire about injuries, substantial injuries, injury severity and subjective well-being (scale 0-100). Results: A linear mixed model showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Those athletes reporting anxiety symptoms had a higher risk of injury (Relative Risk 2.3, 95% CI: 2–2.6, p < 0.001), while no increased risk was observed for those reporting depressive symptoms (RR 1.1, 95%CI: 0.9–1.3). Another report on elite athletes investigated the role for subjective wellbeing in the risk of injury during the season [ 52 ]. The Oslo Sports Trauma Research Centre (OSTRC) Overuse Injury Questionnaire was used for either monitoring injuries or assessing the wellbeing of the athlete.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those athletes reporting anxiety symptoms had a higher risk of injury (Relative Risk 2.3, 95% CI: 2–2.6, p < 0.001), while no increased risk was observed for those reporting depressive symptoms (RR 1.1, 95%CI: 0.9–1.3). Another report on elite athletes investigated the role for subjective wellbeing in the risk of injury during the season [ 52 ]. The Oslo Sports Trauma Research Centre (OSTRC) Overuse Injury Questionnaire was used for either monitoring injuries or assessing the wellbeing of the athlete.…”
Section: Resultsmentioning
confidence: 99%
“…Correlation analysis showed also a negative association between wellbeing score and severity score (r = −0.32, p < 0.001), with a mixed model suggesting the influence of sex ( p = 0.019) and severity score ( p < 0.001) on wellbeing. Furthermore, mixed models showed that wellbeing score measured at the week before injury predicted injury (logistic mixed, p = 0.036) and injury severity (linear mixed, p = 0.010) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In adolescent athletes of various sports, it was found that lower well-being, represented through wellness scores, was present in injured athletes. 47 Additionally, the authors reported increased injury risk for the week after a low well-being score. 47 The negative effects of high workloads on athlete reported wellness has been documented in previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…47 Additionally, the authors reported increased injury risk for the week after a low well-being score. 47 The negative effects of high workloads on athlete reported wellness has been documented in previous studies. 43,51 Similarly, in the current study when adjusted for arm health, higher chronic load was associated with increased throwing-related injuries.…”
Section: Discussionmentioning
confidence: 97%